Genre theory in information studies - Andersen, Jack (Studies in Information, 2015)
Studies in information publishes monographs on critical issues in the information society. The book series is concerned with all aspects of information; its nature, politics, institutions, usages, and technologies, and it presents research from a wide range of disciplinary traditions. Previously published as Library and information science, it is a fully peer-reviewed and high impact outlet for research in the field of information. This new volume, edited by Jack Andersen, is the first to be published under the new series name Studies in Information. The book highlights the important role genre theory plays within information studies. It illustrates how modern genre studies inform and enrich the study of information, and conversely how the study of information makes its own independent contributions to the study of genre. Various original contributions scrutinize core aspects of information and knowledge organization, such as information systems and distributed authorship; personal information management; and records management in organizations, all through the lens of genre.
Keywords: Business & Economics : Information Management; Library, archive & information management; Information science : Research; Information science